Risk factors and prevention strategy for patient dissatisfaction after transforaminal lumbar interbody fusion: a single-center retrospective study - Yang, Lixin; Guo, Zhao; Qiao, Yuhao; Guo, Jichao; Li, Jiaqi; Wang, Wei (Frontiers in Surgery, 2025)
BackgroundFor patients who received transforaminal lumbar interbody fusion (TLIF) treatment for lumbar disc herniation, most of them can achieve good results, but there were still some patients who were not satisfied with the surgical results. The purpose of this study is to explore the factors that contribute to patient dissatisfaction after TLIF.MethodsFrom March 2018–December 2021, patients with lumbar disc herniation who received TLIF treatment were included in this study. Clinical data from preoperative and postoperative 2-year follow-up were analyzed. Associations between clinical variables and function of postoperative were examined in univariate and multivariate analysis.ResultOf all the 625 patients, including 296 (47.4%) male patients and 329 (52.6%) female patients. According to patient satisfaction index (PSI), patients were divided into two groups, 529 patients in satisfied group showing 1 or 2 stage in PSI and 96 patients in dissatisfied group showing 3 or 4 stage in PSI. Univariate analysis showed that body mass index (BMI), preoperative pain time, postoperative visual analog scale (VAS)-back, intraoperative bleeding volume, postoperative rehabilitation training, feel depression and symptom recurrence were related with patient's level of satisfaction 2 years after discectomy. When incorporated into a multivariate logistic regression analysis, it was found that BMI, preoperative pain duration, postoperative rehabilitation training, feel depression and symptom recurrence were individually correlated with patient dissatisfaction 2 years after discectomy.ConclusionThis study indicates that the factors that leading to postoperative dissatisfaction of patients include obesity, preoperative pain duration lasting no less than 6 months, feel depression and symptom recurrence. While postoperative rehabilitation training for three months is a protective factor.